Antagonism of Cannabinoid Receptor 1 Attenuates the Anti-Inflammatory Effects of Electroacupuncture in a Rodent Model of Migraine. Issue 6 (December 2016) - Zhang, Hui; He, Shengdong; Hu, Youping; Zheng, Hui
Background: The anti-nociceptive effects of electroacupuncture (EA) in migraine have been documented in multiple randomised controlled trials. Neurogenic inflammation plays a key role in migraine attacks, and the anti-inflammatory effects of acupuncture have been associated with the type 1 cannabinoid (CB1) receptor. Objective: To investigate whether CB1 receptors mediate the anti-inflammatory effects of EA on migraine attacks. Methods: A migraine model was produced in Sprague-Dawley rats by unilateral electrical stimulation of the trigeminal ganglion (TGES). Rats received EA daily on the 5 days preceding TGES with (TGES+EA+SR141716 group) or without (TGES+EA group) intraperitoneal injections of the CB1 receptor antagonist SR141716. Another group of TGES rats (TGES+MA group) and a non-TGES sham-operated group of rats (Sham+MA group) received minimal acupuncture (MA). Calcitonin gene-related peptide (CGRP) and prostaglandin E2 (PGE2) concentrations were determined in serum obtained from the ipsilateral jugular vein at initiation of TGES and 5 min after. Postmortem interleukin (IL)-1β and cyclooxygenase (COX)2 protein levels in the trigeminal ganglion (TG) and plasma protein extravasation (PPE) in the dura mater were assessed. Results: TGES induced increases in serum CGRP and PGE2 levels (TGES+MA vs baseline and vs Sham: all p<0.001), as well as IL-1β and COX2 protein expression in the TG, and neurogenic PPE levels (TGES+MA vs Sham+MA: all p<0.001). EA attenuated TGES-induced increases in the levels of these proteins (TGES+EA vs TGES+MA: all p<0.001). CB1 receptor antagonism reversed the effects of EA (TGES+EA+SR141716 vs TGES+EA: all p<0.05). Conclusions: CB1 receptors appear to mediate anti-inflammatory effects of EA in a rat model of migraine.